Botulinum toxin treatment of dystonic anterocollis: What to inject. (July 2021) - Marion, Marie-Helene; Hicklin, Lucy A.
Abstract: Background: Anterocollis (AC) is a rare form of cervical dystonia, which responds poorly to botulinum toxin treatment. Objectives: To recognise the different clinical phenotypes of AC and to detail the selection of muscles from the results of treating a cohort of 15 AC patients with Botulinum Toxin. Methods: The study was performed using prospectively collected data. We included 15 patients with cervical dystonia and AC posture, treated between 2016 and 2019 in our joint Neuro-ENT clinic. We excluded patients with posterior cervical muscle weakness and patients with Parkinsonism. We characterised the primary dystonic posture of every AC patient as posterior sagittal shift, head flexion or neck flexion, or a combination of the three. Results: All AC patients had a more widespread dystonic picture with a majority having Meige syndrome, but AC was the most problematic feature. Treatment with botulinum toxin required the injection not only of the deep cervical flexor (DCF), but also the sterno-cleido-mastoid (SCM) and moreover the supra-hyoid (SH) muscles. The choice between the longus capiti and the longus colli depended on the AC posture. Half of the patients had a dramatic improvement with 90% satisfaction or above. Conclusion: AC posture is a complex but treatable type of CD. A joint Neuro-ENT clinic is an ideal setting in which to target all the dystonic muscles. This allows the injection of the longus capiti (under nasal endoscopic approach) as well as the supra-hyoid and SCM muscles in the same session. Highlights: Anterocollis is a complex but treatable type of cervical dystonia. Botulinum toxin injection for anterocollis in the deep cervical flexor, the sterno-cleido-mastoid and the supra-hyoid muscles. The choice between the longus capiti and the longus colli depends on the anterocollis posture. Half of the patients had a dramatic improvement with 90% satisfaction or above.